Current Approach to Phototherapy Applications in Dermatology Practice: Part 1. History, Lamps, Ultraviolet Radiation Levels Measurement and Phototherapy Modalities - SEÇKİN GENÇOSMANOĞLU, DİLEK (WOLTERS KLUWER MEDKNOW PUBLICATIONS, 2017)
Lately, important advances take place in dermatological treatment. Phototherapy, as one of the oldest treatment modalities in the history of dermatology, does not fall behind these advances; on the contrary, it is still used widely in the treatment of many skin diseases with the advantages of being effective and safe. This article aims to give practical and basic information about artificial ultraviolet sources, dosimetry and calibration standards of these sources and ultraviolet treatment protocols, starting with the history of current phototherapy modalities.
Keywords: Dosimetry; calibration; history; psoralen ultraviolet A; ultraviolet B; phototherapy; CHRONIC PLAQUE PSORIASIS; BAND UV-B; EXCIMER-LASER; PHOTOCARCINOGENIC RISK; PSORALEN-ULTRAVIOLET; BRITISH ASSOCIATION; GOECKERMAN THERAPY; TL-01 PHOTOTHERAPY; CANCER-RISK; SKIN-CANCER